Frontal Brain Activity and Subjective Arousal During Emotional Picture Viewing in Nightmare Sufferers - Carr, Michelle; Summers, Richard; Bradshaw, Ceri; Newton, Courtney; Ellis, Leslie; Johnston, Erin; Blagrove, Mark (Frontiers in Neuroscience, 2020)
Nightmares are intensely negative dreams that awaken the dreamer. Frequent nightmares are thought to reflect an executive deficit in regulating arousal. Within diathesis-stress frameworks, this arousal is specific to negative contexts, though a differential susceptibility framework predicts elevated arousal in response to both negative and positive contexts. The current study tested these predictions by assessing subjective arousal and changes in frontal oxyhemoglobin (oxyHB) concentrations during negative and positive picture-viewing in nightmare sufferers (NM) and control subjects (CTL). 27 NM and 27 CTL subjects aged 18-35 rated subjective arousal on a 1-9 scale following sequences of negative, neutral and positive images; changes in oxyHB were measured by Near-Infrared Spectroscopy (NIRS) using a 2x4 template on the frontal pole. Participants also completed the Highly Sensitive Person Scale, a trait marker for Differential Susceptibility; and completed a dream diary reporting negative and positive dream emotionality. The NM group had higher trait sensitivity, yet higher ratings of negative but not positive emotion in diary dreams. NM compared to CTL subjects reported higher subjective arousal in response to picture-viewing regardless of valence. Dysphoric dream distress, measured prospectively, was negatively associated with frontal activation when viewing negative pictures. Results suggest NM sufferers are highly sensitive to images regardless of valence according to subjective measures, and there is a neural basis to level of trait and prospective nightmare distress. Future longitudinal or intervention studies should further explore positive emotion sensitivity and imagery in NM sufferers.